2014
DOI: 10.3390/w7010188
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Nitrate Sources of the Yili River in the Taihu Lake Watershed: A Dual Isotope Approach

Abstract: Abstract:As the third largest freshwater lake in China, Taihu Lake has experienced severe cyanobacterial blooms and associated water quality degradation in recent decades, threatening the human health and sustainable development of cities in the watershed. The Yili River is a main river of Taihu Lake, contributing about 30% of the total nitrogen load entering the lake. Tracing the nitrate sources of Yili River can inform the origin of eutrophication in Taihu Lake and provide hints for effective control measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…A dual isotope bi-plot approach (δ 15 N-NO3 − and δ 18 O-NO3 − ) is adopted to qualitatively identify predominant NO3 − sources for surface water in different periods [4]. The ranges of δ 15 N-NO3 − and δ 18 O-NO3 − in precipitation were from −10.9‰ to 6.8‰ and from 49.8‰ to 70.2‰, respectively.…”
Section: Nitrate Isotope Characteristics and Qualitative Analysis Of mentioning
confidence: 99%
See 3 more Smart Citations
“…A dual isotope bi-plot approach (δ 15 N-NO3 − and δ 18 O-NO3 − ) is adopted to qualitatively identify predominant NO3 − sources for surface water in different periods [4]. The ranges of δ 15 N-NO3 − and δ 18 O-NO3 − in precipitation were from −10.9‰ to 6.8‰ and from 49.8‰ to 70.2‰, respectively.…”
Section: Nitrate Isotope Characteristics and Qualitative Analysis Of mentioning
confidence: 99%
“…During nitrification process (NH 4 + oxidized to NO 3 − ), it has revealed that there exists considerable .4‰, which were calculated using δ 18 O in precipitation and surface water in the study area. Therefore, the range of δ 18 O derived from nitrification of NH 4 + was from −3.3‰ to +10.78‰, which was close to (but a little narrower than) the values found in other studies (−5‰-+15‰) [43,44].…”
Section: Nitrification Processes Of Ammoniamentioning
confidence: 99%
See 2 more Smart Citations
“…In water studies, chloride is generally used as a conservative tracer of mixing within the streams, as it is an effective indicator of sewage and dilution effects which has minimal affects from physical, chemical and biological processes [52]. Hence, the ratio of NO 3 -N/Cl − was also considered for the study of N dynamics and sources.…”
Section: Nitrate Sources Through Isotopic Composition In Stream Watermentioning
confidence: 99%